2003
DOI: 10.1016/s0022-5223(03)00214-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychometric outcome following aortic arch surgery: a prospective randomized trial of retrograde cerebral perfusion

Abstract: Hypothermic circulatory arrest plus/minus retrograde cerebral perfusion is associated with a high incidence of neuropsychometric change despite ostensibly normal clinical outcomes and apparently safe arrest duration. Retrograde cerebral perfusion did not improve outcome in this small study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 28 publications
1
28
0
1
Order By: Relevance
“…The overall incidence of neurological injury in terms of stroke, transient neurological deficit, and neuropsychometric deficit in this study is comparable with the reported literature, [1][2][3][4]12 but it is higher than that observed in 1 previous randomized study. 29 However, the sample size in that study was also small and a different battery of tests was used.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The overall incidence of neurological injury in terms of stroke, transient neurological deficit, and neuropsychometric deficit in this study is comparable with the reported literature, [1][2][3][4]12 but it is higher than that observed in 1 previous randomized study. 29 However, the sample size in that study was also small and a different battery of tests was used.…”
Section: Discussionsupporting
confidence: 89%
“…Although a high incidence of neuropsychometric deficit after HCA has previously been demonstrated, 3,4,12 large numbers would also be required to demonstrate a clinical difference between groups. Cerebral blood flow and transcranial oxygen extraction have been used in a number of studies as surrogate markers of cerebral metabolism.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The largest influence on QoL in this study is therefore related to the mental and psychic brain performance. 1,16 We have reasons to suspect that low average scores of QoL may be the main consequence of diffuse brain damage induced by DHCA. 9 This observation is further supported by the fact that the application of ACP resulted in a significant improvement of QoL scores for all DHCA periods (Ͻ20, 20 to 29, Ն30 minutes) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Interruption of cerebral blood flow has been associated with a high incidence of neurologic injury because the brain is susceptible to ischemic injury within minutes of the onset of circulatory arrest as a result of its high metabolic rate and limited reserves (Harrington et al, 2003). The physiologic basis for hypothermia as a neuroprotective strategy is its ability to reduce the cerebral oxygen metabolic rate and the accumulation of toxic metabolites.…”
Section: Deep Hypothermic Circulatory Arrestmentioning
confidence: 99%